Simultaneous Round Table Role Answers Solve the Equation: 2(3𝑥 − 4) = 1 6 (𝑥 − 3). Use the following first step: Student 1: Distribute the 2. Student 2: Divide by 2. Student 3: Multiply by 6. Student 4: Distribute 1 6 Answers will vary, following are possible answers: Student 1: Step Reason 2(3𝑥 − 4) = 1 (𝑥 − 3) 6 1 6x – 8 = 6 (𝑥 − 3) 6(6x -8) = x - 3 36x – 48 = x - 3 35x – 48 = -3 35x = 45 X= 45 35 𝑥= Student 2: 9 7 Step 2(3𝑥 − 4) = 1 12(3x – 4) = x-3 36x – 48 = x -3 35x – 48 = -3 35x = 45 45 35 Distributive Property Multiplication Property of Equality Distributive Property Subtraction (or Addition) Property of Equality Addition Property of Equality Division (or multiplication) Property of Equality Simplify Reason (𝑥 − 3) 6 1 3x – 4 = 12(x – 3) X= Given Given Division (or multiplication) property of equality Multiplication Property of Equality Distributive Property Subtraction (or Addition) Property of Equality Addition Property of Equality Division (or multiplication) Property of Equality 𝑥= 9 7 Simplify Student 3: Step 2(3𝑥 − 4) = Reason 1 (𝑥 − 3) 6 12 (3x – 4) = x – 3 36x – 48 = x -3 35x – 48 = -3 35x = 45 X= 45 Given Multiplication Property of Equality Distributive Property Subtraction (or Addition) Property of Equality Addition Property of Equality Division (or multiplication) Property of Equality 35 9 7 Simplify Step Reason 𝑥= Student 4: 2(3𝑥 − 4) = 1 (𝑥 − 3) 6 1 1 2 (3x – 4) = 6x - 2 1 1 6x – 8 = 6x - 2 1 1 6𝑥 − 𝑥 = 8 − 6 2 35 15 𝑥= 6 2 90 𝑥= 70 9 𝑥= 7 Given Distributive Property Distributive Property Addition Property of Equality Simplify Multiplication Property of Equality Simplify